Thermal history recorded by the Apollo 17 impact melt breccia 73217 - Grange, Marion; Nemchin, Alexander; Pidgeon, Robert; Timms, Nicholas Eric; Muhling, J.; Kennedy, Allen (Pergamon-Elsevier Science Ltd, 2009)
Lunar breccia 73217 is composed of plagioclase and pyroxene clasts originating from a single gabbronorite intrusion, mixed with a silica-rich glass interpreted to represent an impact melt. A study of accessory minerals in a thin section from this breccia (73217,52) identified three different types of zircon and anhedral grains of apatite which represent distinct generations of accessory phases and provide a unique opportunity to investigate the thermal history of the sample. Equant, anhedral zircon grains that probably formed in the gabbronorite, referred to as type-1, have consistent U?Pb ages of 4332 7 Ma. A similar age of 4335 5 Ma was obtained from acicular zircon (type-2) grains interpreted to have formed from impact melt. A polycrystalline zircon aggregate (type-3) occurs as a rim around a baddeleyite grain and has a much younger age of 3929 10 Ma, similar to the 3936 17 Ma age of apatite grains found in the thin section. A combined apatite-type-3 zircon age of 3934 12 Ma is proposed as the age of the Serenitatis impact event and associated thermal pulse. X-ray mapping andelectron probe analyses showed that Ti is inhomogeneous in the zircon grains on the sub-micrometer scale. However, model temperatures estimated from SHRIMP analyses of Ti-concentration in the 10 lm diameter spots on the polished surfaces of type-1 and type-2 zircons range between about 1300 and 900 C respectively, whereas Ti-concentrations determined for the type-3 zircon are higher at about 1400?1500 C. A combination of U?Pb ages, Ti-concentration data and detailed imaging and petrographic studies of the zircon grains shows that the gabbronorite parent of the zircon clasts formed shortly before the 4335 5 Ma impact, which mixed the clasts and the felsic melt and projected the sample closer to the surface where fast cooling resulted in the crystallization of acicular zircon (type-2). The 3934 12 Ma Serenitatis event resulted in partial remelting of the glass and formation of polycrystalline zircon (type-3). This event also reset the U?Pb system of apatite, formed merrillite coronas around some apatite grains, and probably re-equilibrated some pyroxenes in the clasts. Although there have been arguments for pre-3.9 Ga impacts based on other types of samples, the age of the acicular zircon at 4335 5 Ma provides the first evidence of impact melt significantly predating the lunar cataclysm. Our data, combined with other chronological results, demonstrate the occurrence of pre-3.9 Ga impacts on the Moon and suggest that the lunar impact history consisted of a series of intense bombardment episodes interspersed with relatively calm periods of low impact flux.